Analysis of the Czech Unemployed and Employed Using Multivariate Methods - Musilová, Klára; Šulc, Zdeněk; Kaspříková, Nikola; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
The study is based on the survey Cooperation 2015 which was conducted by IPSOS,s.r.o. for Fond dalšího vzdělávání. The main purpose of this thesis is to analyze opinions, feelings and experience of the unemployed and employed people in the Czech Republic in 2015. The thesis is divided into three main parts. The first one describes a theoretical background for used analyses, such as correspondence and loglinear analysis. Also, it consists of a brief introduction to categorical variables and contingency tables. The second one describes the Cooperation survey 2015 and the specific analyzed variablesfrom this survey that were chosen for the analysis. The final part of the thesis is an application of presented methods on the survey data. All calculations were made usingthe software IBM SPSS 20.
Vedoucí práce: Zdeněk Šulc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: statistika [obor dipl. práce]; diplomové práce; master's theses